MiR-9, miR-21, miR-27b, and miR-34a Expression in HPV16/58/52-Infected Cervical Cancer. (17th September 2020) - Liu, Mi; Wang, Wei; Chen, Haixing; Lu, Yi; Yuan, Daisha; Deng, Yongjiu; Ran, Danlu
Abstract : The aim of this study was to observe the expression of miR-9, miR-21, miR-27b, and miR-34a related with E6/E7 in HPV16-, HPV52-, and HPV58-infected cervical cancer patients and explore their possible role in cervical cancer with HPV infection. The expression levels of 4 miRNAs were detected in cervical exfoliated cells using qRT-PCR. In the current study, miR-34a expression was significantly upregulated in HPV-positive cervical cancer compared with the HPV-negative healthy population and HPV-positive CIN, but just the expression of miR-34a in HPV16 cervical cancer was statistically significant, and the expression of HPV52 and HPV58 was not statistically significant. The expression of miR-21 increased in HPV-positive cervical cancer compared with HPV-positive CIN, but only HPV16-infected cervical cancer had statistical significance compared with HPV16-infected CIN. By observing the change trend of each subtype group, we can show that the expression of miR-9 in HPV16 CIN was opposite to the other subtypes, and it was upregulated, compared with HPV58 CIN, and significantly increased. The level change of miR-27b in HPV58 cervical cancer and HPV58 CIN was opposite to the other subtypes; unlike the expression of miR-27b which was upregulated in HPV16 and HPV52 infected, it was downregulated compared with Normal. We also found that the expression of miR-34a and miR-9 was contrary to other studies. These findings indicate that the upregulated miR-21 expression may be a biomarker to distinguish between CC and CIN. miR-34a in HPV infection, especially in HPV16 infection, might be related to the occurrence and development of cervical cancer. The infection of different subtypes may play different roles in disease by activating different mechanisms; miRNAs play a very complex role in tumorigenesis and development, and there may be multiple targets in which multiple mechanisms play a role.